Implementing Security and Trust in IoT/M2M using Middleware - Castilho, Sergio D. [UNESP] (2020)
Machine to Machine (M2M) a sub area of Internet of Things (IoT) will link billions of devices or things distributed around the world using the Internet. These devices when connected exchange information obtained from the environment such as temperature or humidity from industrial or residential control process. Information Security (IS) and Trust are one of the fundamental points for users and the industry to accept the use of these devices with Confidentiality, Integrity, Availability and Authenticity. The key reason is that most of these devices use wireless media especially in residential and smart city environments. The overall goal of this work is to implement a Middleware Security to improve Safety and Security between the control network devices used in IoT/M2M and the Internet for residential or industrial environments. This implementation has been tested with different protocols as CoAP and MQTT, a microcomputer with free Real-Time Operating System (RTOS) implemented in a Raspberry Pi Gateway Access Point (RGAP), Network Address Translator (NAT), IPTable firewall and encryption is part of this implementation for secure data transmission.